Characteristic of Natural and Acid-activated Clay From Hatu Village, Mollucas Province: FTIR, XRD, XRF, SEM-EDX, TEM, and BET Analysis - Sekewael, Serly Jolanda; Maahury, Mirella Fonda (Molekul, 2023)
Research on the chemical and physical characteristics of natural and acid-activated clay from Hatu Village had been carried out using FTIR, XRD, XRF, SEM-EDX, TEM, and BET surface area analyzer instruments. The natural clay had activated with 0.25 M sulfuric acid for 3 hours using the reflux method, then calcined with 700 Watt microwave radiation for 10 minutes. Overall, FTIR data show tetrahedral and octahedral functional groups that create clay minerals. There is a decrease in absorption intensity due to acid's influence, which dissolves cations in the octahedral and interlayer clay. The XRD analysis shows the Hatu natural clay contains montmorillonite, alumina, kaolinite, quartz, and illite minerals. Broadening and decreasing the intensity of diffraction peaks due to treatment by acid and calcination. SEM images of natural clay before and after activation-calcination shows the morphology of porous and layered material, while the mapping of the surface of natural clay shows irregular and rough material topography. The EDX spectra showed four elements with the most extensive composition: O, Si, Al, and Fe. XRF data confirmed three components that have the highest mass percent, namely SiO2, Al2O3, and Fe2O3. Dealumination occurs at 0.95% due to activation by sulfuric acid along with calcination. TEM images clearly show the multilayered silicate materials. The higher nitrogen gas uptake by activated-calcinated natural clay is proportional to the large surface area and total pore volume.